On the use of an enhanced transverse shear strain shell element for problems involving large rotations - R. A. Fontes Valente (2003)
This paper presents the extension of a previously developed formulation for shell elements in order to account for non-linear geometric effects, particularly in the presence of large rotations. To eliminate transverse shear locking, the developed shell formulation provides an enlargement of the transverse shear strain field coming from the usual degenerated concept. Doing so, additional transverse shear strain terms are included into the original displacement-based functional, following the enhanced strain approach. To reproduce the behavior of shell structures under large rotations and displacements, a rotation-free configuration is considered, where constitutive relations are stated. Dealing with finite incremental rotations, a singularity-free procedure is employed, characterizing the evolution of normal vectors to shell's mid-surface. Representative non-linear examples are considered, providing the validation of the enhanced shell element as well as the algorithmic procedures implemented, when compared to other formulations in the literature.